Pengaruh Ambivalensi Regulasi dan Praktik Korupsi Terhadap Krisis Kepercayaan Publik dalam Konteks Reformasi Kepolisian Negara Republik Indonesia - Ratna Indriasari; Hestiwati Basir (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2026)
This study analyzes the impact of regulatory ambivalence and corrupt practices on the crisis of public trust in the reform agenda of the Indonesian National Police (Polri). Althoughreforms have been underway for more than two decades, the prevalence of corruption and lowaccountability indicate a dysfunctional cycle that hinders institutional transformation. Using anexplanatory qualitative approach, this study unravels the chain of causality behind thephenomenon of the crisis of trust. The results show that the public trust crisis is rooted in theinstitution's failure to close ambiguous regulatory loopholes, which are then exploited throughsystemic corruption practices. Restoring public trust requires comprehensive deregulation ofambivalent internal policies and consistent law enforcement to break the dysfunctional cyclethrough a structural causality model.